1978
DOI: 10.1115/1.3450788
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Mean Absorption Coefficients of Luminous Flames and Smoke

Abstract: A simple procedure has been developed for the calculation of the Planck mean emission and absorption coefficients and the Rosseland mean absorption coefficient for infrared radiation of the soot-gas mixtures commonly occurring in luminous flames and smoke. Specific results are presented for mixtures involving carbon dioxide, water vapor and carbon soot, the dominant species in most combustion systems. The close agreement between the various averages clearly demonstrates the usefulness of the mean absorption co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…For simplicity in presenting the role of radiative heat loss on the dynamics of flame ball formation, the results given in this section are based on calculations employing optically thin radiation with the Planck mean absorption/emission coefficients of Hubbard and Tien [20]. With respect to the scope of this work, the effects of reabsorption are mainly quantitative and do not affect the discussion of the underlying physical mechanisms.…”
Section: Phenomena and Concentration Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity in presenting the role of radiative heat loss on the dynamics of flame ball formation, the results given in this section are based on calculations employing optically thin radiation with the Planck mean absorption/emission coefficients of Hubbard and Tien [20]. With respect to the scope of this work, the effects of reabsorption are mainly quantitative and do not affect the discussion of the underlying physical mechanisms.…”
Section: Phenomena and Concentration Limitsmentioning
confidence: 99%
“…Radiation heat loss is considered to be emitted only from H 2 O. Planck mean absorption/emission coefficients of Hubbard and Tien (H&T) [20], based on a wideband model, are compared with those of Ju et al [21], based on a statistical narrowband (SNB) model. For optically thick radiation, radiative transport including both emission and absorption is computed using the SNB model with exponential-tailed inverse line strength distribution [22].…”
Section: Problem Definitionmentioning
confidence: 99%
“…For simplicity in presenting the role of radiative heat loss on the flame dynamics, the results given in this section are based on calculations employing optically thin radiation with the Planck mean absorption/ emission coefficients of Hubbard and Tien (1978), which also represents the most severe heat loss condition. With respect to the scope of this work, the effects of reabsorption have been found to be mainly quantitative (e.g., limited calculations revealed that reabsorption can shift the boundaries) and do not affect the discussion of the underlying physical mechanisms.…”
Section: Radiative Effects On Flammability Boundariesmentioning
confidence: 99%
“…Radiation heat loss is considered to be emitted only from H 2 O. Planck mean absorption/emission coefficients based on a wideband model are taken from Hubbard and Tien (1978).…”
Section: Problem Definitionmentioning
confidence: 99%
“…It has been shown that CO 2 and H 2 0 emission is negligible compared with soot emission (3) which is characterized by fv' the fraction of the flame volume occupied by solid carbon particles (4). While much progress has been made in developing procedures for calculating flame radiation (5,6), it is not possible to predict fv in fires because the soot formation and destruction mechanisms have not been quantified (7). It is therefore necessary to measure ~ situ flame carbon particles.…”
Section: Introductionmentioning
confidence: 99%